2014
DOI: 10.1037/a0036337
|View full text |Cite
|
Sign up to set email alerts
|

Short-term perceptual learning in visual conjunction search.

Abstract: Although some studies showed that training can improve the ability of cross-dimension conjunction search, less is known about the underlying mechanism. Specifically, it remains unclear whether training of visual conjunction search can successfully bind different features of separated dimensions into a new function unit at early stages of visual processing. In the present study, we utilized stimulus specificity and generalization to provide a new approach to investigate the mechanisms underlying perceptual lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 26 publications
13
30
0
Order By: Relevance
“…A somewhat contrasting view has come from Su et al (2014). These authors examined the effect of training on conjunction search.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A somewhat contrasting view has come from Su et al (2014). These authors examined the effect of training on conjunction search.…”
Section: Discussionmentioning
confidence: 99%
“…In the Frank et al (2014) study, observers learned over the course of eight sessions over eight days. Su et al (2014) tested observers in one experimental session lasting 40-50 min. Thus, it might be that the mechanisms underlying efficient conjunction search and the deployment of object-based attention dynamically change over the course of learning and depend on the robustness and quality of feature associations and object representations (Chen, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some behavioral studies found that visual PL depends on perceptual constancy (Garrigan & Kellman, 2008) and is diagonal mirror-transferable (Chen et al, 2008). Accordingly, it was also proposed that visual PL occurs at the middle visual stages, such as the extrastriate cortex including V2-V4, where neurons are characterized by both orientation/location selectivity and more complex properties (Chen et al, 2008), and involves feature-based selective attention (Su et al, 2014). Several brain imaging studies have directly investigated the brain mechanisms of specificity and generalization of human visual PL (e.g., Ding et al, 2003;Schiltz et al, 1999;Song et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Detectability relies on not only physical properties of the stimulus (e.g., physical salience) but also observers’ prior experience (e.g., learning history). For example, previous studies reported that detectability of a stimulus could be enhanced through perceptual learning (Su et al, ; Watanabe, Náñez, & Sasaki, ). In Qu et al’s study (), although subjects’ performance improved through training, the final accuracy ( p’ ) of detecting a trained triangle in a visual display was only 0.345, which was far less than detecting a feature singleton (e.g., Girelli & Luck, ), indicating that the detectability of a trained triangle was very low even after extensive training.…”
Section: Introductionmentioning
confidence: 99%